Long-term impact of youth minimum wages: evidence from two decades of individual longitudinal data - Ana Rute Cardoso (Institute for the Study of Labor (IZA), 2009)
This paper quantifies the long-run impact of exposure to youth minimum wages and sheds light on its mechanisms. It uses remarkable longitudinal data spanning for twenty years and explores legislative changes that define groups of teenagers exposed for different durations. After controlling for the contemporaneous impact of the minimum wage, its long-run impact translates into: an overall wage premium, consistent with an upgrading in the quality of jobs offered; a flatter tenure-earnings profile, consistent with lower initial investment in firm-specific training. Interestingly, the overall wage premium increases with exposure and the tenure-earnings profile is flatter the longer the exposure.
urn:nbn:de:101:1-20090622190
Keywords: J08; J31; J24; J38; 330; Skill formation; human capital investment; on-the-job-training; career; long-term; linked employer-employee data; Jugendliche Arbeitskräfte; Mindestlohn; Wirkungsanalyse; Berufsbegleitende Ausbildung; Bildungsinvestition; Erwerbsverlauf; Bildungsertrag; Portugal